Serum lactate dehydrogenase level in pre-eclampsia and its correlation with maternal and fetal outcome - Vyas, Niyanta P.; Gopalakrishna, Nandini; Fernandes, Jessica (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Hypertensive disorders are the most common medical disorders during pregnancy. It increases maternal and perinatal morbidity and mortality. The incidence is 7 to 10%. Identifying high risk patients and close monitoring can reduce the complications. Lactate dehydrogenase is a useful biochemical marker and can be used to evaluate maternal complications like Disseminated intravascular coagulation (DIC), HELLP syndrome (Haemolysis, elevated liver enzymes and lowered platelets), pulmonary edema, renal failure and fetal complications like Fetal growth restriction (FGR) APGAR score ≤7 at 5 min and Neonatal intensive care unit (NICU) admissions. The objective of this study was to estimate serum Lactate dehydrogenase levels (LDH) in pre-eclampsia patients and study the correlation between increased LDH levels and maternal and fetal outcome. Methods: It was a prospective study from October 2015 to May 2017 at M. S. Ramaiah medical college and hospitals, Bangalore. Results: The incidence of maternal and foetal complications was increased with higher serum LDH levels. With serum LDH >than 600 IU/l the incidence of HELLP syndrome, DIC, pulmonary edema was statistically significant. It also correlated with increased creatinine levels and decreased platelets with p value<0.001. The foetal complications including FGR NICU admission and Apgar score <7 at 5 min was statistically significant. The liver enzymes and serum creatinine correlated with increased LDH levels. Conclusions: Maternal and foetal complications are increased with raised LDH levels, and it can be used as a biochemical marker to achieve a better outcome.